Platelet-Rich Plasma Derived Growth Factors Contribute to Stem Cell Differentiation in Musculoskeletal Regeneration - Qian, Yun; Han, Qixin; Chen, Wei; Song, Jialin; Zhao, Xiaotian; Ouyang, Yuanming; Yuan, Weien; Fan, Cunyi (Frontiers in Chemistry, 2017)
Stem cell treatment and platelet-rich plasma (PRP) therapy are two significant issues in regenerative medicine. Stem cells such as bone marrow mesenchymal stem cells, adipose-derived stem cells and periodontal ligament stem cells can be successfully applied in the field of tissue regeneration. PRP, a natural product isolated from whole blood, can secrete multiple growth factors (GFs) for regulating physiological activities. These GFs can stimulate proliferation and differentiation of different stem cells in injury models. Therefore, combination of both agents receives wide expectations in regenerative medicine, especially in bone, cartilage and tendon repair. In this review, we thoroughly discussed the interaction and underlying mechanisms of platelet-rich plasma derived growth factors with stem cells, and assessed their functions in cell differentiation for musculoskeletal regeneration.